Applications of Cas9 as an RNA-programmed RNA-binding protein - Nelles, David A. (Bioessays, 2015)
The Streptococcus pyogenes CRISPR-Cas system has gained widespread application as a genome editing and gene regulation tool as simultaneous cellular delivery of the Cas9 protein and guide RNAs enables recognition of specific DNA sequences. The recent discovery that Cas9 can also bind and cleave RNA in an RNA-programmable manner indicates the potential utility of this system as a universal nucleic acid-recognition technology. RNA-targeted Cas9 (RCas9) could allow identification and manipulation of RNA substrates in live cells, empowering the study of cellular gene expression, and could ultimately spawn patient- and disease-specific diagnostic and therapeutic tools. Here we describe the development of RCas9 and compare it to previous methods for RNA targeting, including engineered RNA-binding proteins and other types of CRISPR-Cas systems. We discuss potential uses ranging from live imaging of transcriptional dynamics to patient-specific therapies and applications in synthetic biology.